Decentralization now! For the real development of the country and the effective construction of the social and democratic state governed by the rule of law - Gonzales Ojeda, Magdiel (2018)
Centralization and decentralization as well as deconcentration in the administrative division of the Peruvian state have been conditioned by political, social, economic and religious factors; In brief, by factors of power. The execution of these policies in the Peruvian context has brought serious difficulties in the development of the country. In this article, the author studies the Peruvian model and its adaptations taking into account the historical data. Finally, he proposes the reform challenges that must be faced in decentralization and the strengthening of regionalization, both understood as necessary institutional processes to achieve the integral development of the country.